Building Theoretical and Empirical Bridges Across Levels: Multilevel Research in Management - Hitt, Michael A.; Beamish, Paul W.; Jackson, Susan E.; Mathieu, John E. (Academy of Management Journal, 2007)
Most management problems involve multilevel phenomena, yet most management research uses a single level of analysis. A micro or a macro lens alone yields incomplete understanding at either level. Multilevel research addresses the levels of theory, measurement, and analysis required to fully examine research questions. This forum presents multilevel research on bribery, national identity, team boundary spanning, professional role identity, organizational citizenship, interorganizational exchanges, and divestitures. To enrich the impact of future management research, we recommend (1) applying multilevel designs to existing models (2) considering bottom-up effects, (3) collaborating across disciplines on multidisciplinary topics, and (4) addressing major real-world problems via multilevel approaches.